Enhanced electron-magnon scattering in ferromagnetic thin films and the breakdown of the Mott two-current model - Rowan-Robinson, R.M.; Hindmarch, A.T.; Atkinson, D. (Physical review B - Condensed Matter and Materials Physics, 2014)
Electron-magnon spin-flip scattering in thin films was studied by investigating the thickness dependence of the anisotropic magnetoresistance (AMR) effect and spin-wave stiffness. The absolute resistivity change due to the AMR effect (Δρ) in Ni, Ni:V, and Ni:Cr doped films reduced with film thickness. This loss of AMR is due to enhanced spin-flip scattering, dropping at the same thickness irrespective of dopant. The spin-wave stiffness reduced at the same thickness, confirming enhanced electron-magnon spin-flip scattering. The AMR ratio was fitted with a simple model, in which thickness dependence was included in a spin mixing resistivity term. This analysis gives insight into the fundamental contribution of magnon scattering to the resistivity in thin films, which ultimately has relevance to spin coherence in spintronic devices.
EPrint Processing Status: Full text deposited in DRO